The extent of the impact of receivables on profitability: An applied study of a sample of companies listed on the Amman Stock Exchange for the period (2010-2019) (Entrepreneurship Journal for Finance and Business, 2021)
The study aimed to identify the impact of receivables on profitability in the industrial companies listed on the Amman Financial Market represented by (outstanding receivables, receivables turnover rate) as an independent variable and profitability as a dependent variable, The study was conducted for the period (2010-2019) according to the data available in the Amman Financial Market, In order to achieve the objective of the study and answer its questions to test its hypotheses, the study tested the corporate sector in the Amman Financial Market for a sample of industrial companies, using a set of statistical methods (Pearson Correlation Coefficient).The study reached a number of conclusions, the most important of which is that there is a correlation between receivables and profit indicators, And that there is an impact of receivables indicators on profitability, Where the receivable turnover rate achieved a higher impact on profitability, while the impact of receivables was ranked second, according to the values of the impact factors, The study also recommended that Jordanian companies set a strict credit policy in collecting their outstanding receivables, reduce the collection period for those debts, improve the turnover rate for receivables, increase interest in indicators of those receivables, and resort to improving their financial performance by focusing their management and employing their financial resources in order to reach raising their production levels. And profitability.